2020
DOI: 10.5267/j.msl.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of curriculum design on the employability competency of Malaysian graduates

Abstract: For a country to support the transition of all economic sectors to a knowledge-driven one, attract foreign investment, and drive labor productivity, it is necessary to have access to skilled workforce. However, there is currently an insufficient talent supply and the workforce demand does not match the talent supply because of low graduate employability stemming from the low quality of higher education in Malaysia. To address this issue, this study proposed a conceptual framework to illustrate the perception o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…For instance, UK universities are getting quality students because of their ability to produce employable graduates (Boden & Nedeva, 2010). In addition, Misnia et al (2019) argued that many industries in many nations are now focusing on graduate employability. It is imperative that institutions should be concerned with both the ISSN 1822-7864 (Print) ISSN 2538-7111 (Online) https://doi.org/10.33225/pec/20.78.1000…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, UK universities are getting quality students because of their ability to produce employable graduates (Boden & Nedeva, 2010). In addition, Misnia et al (2019) argued that many industries in many nations are now focusing on graduate employability. It is imperative that institutions should be concerned with both the ISSN 1822-7864 (Print) ISSN 2538-7111 (Online) https://doi.org/10.33225/pec/20.78.1000…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is of great importance that curriculum designers, take cognisance of this need when designing learning programmes. Curriculum should skill-up graduates to participate in the economic system which is being promulgated by the fourth industrial revolution (Misnia et al, 2019). Graduates therefore, need to be thoroughly prepared because the competition for employment is stiff due to the high increase of students registering for higher education and the dynamicity of the work environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings of this study may also provide insights in the existing curriculum by integrating and language for employment especially, the use of lexical items. The existing curriculum can also be restructured based on Malaysian graduate employability competencies as suggested by the study of Misni et al (2020) in preparing students for the 21st century workplace. Therefore, it is essential that undergraduates and recent graduates and are equipped with skills that help them reach peak performance in their workplace by having good employability skills and proficiency.…”
Section: Implications For Higher Education Institutionsmentioning
confidence: 99%
“…In line with MHEM, previous studies by Turner (2014) and Shagrir (2015) have highlighted that MHEM should bolster the recent graduates' employability skills and competency in the language, in this case the use of lexical items. The study by Misni et al (2020) suggested to revamp or restructure the Malaysia Education curriculum to assess the impact of curriculum design on the Malaysian graduate employability competencies in preparing graduates for the 21st century workplace.…”
Section: Introductionmentioning
confidence: 99%
“…Even before the onslaught of the pandemic on Malaysian soil, job seekers and young graduates experienced difficulties in securing their desired jobs (Hanapi & Nordin, 2014;Ismail, 2011). There was also a mismatch between workforce demand and talent supply in Malaysia (Misni et al, 2020;Sulaiman, & Ismail, 2019, Zakariya, 2017. Therefore, amidst the challenging global environment, both employees and organisations must innovate, rebrand, and reposition themselves to stay relevant.…”
Section: Introductionmentioning
confidence: 99%